2007
DOI: 10.1111/j.1467-9280.2007.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

The Level and Nature of Autistic Intelligence

Abstract: Autistics are presumed to be characterized by cognitive impairment, and their cognitive strengths (e.g., in Block Design performance) are frequently interpreted as low-level by-products of highlevel deficits, not as direct manifestations of intelligence. Recent attempts to identify the neuroanatomical and neurofunctional signature of autism have been positioned on this universal, but untested, assumption. We therefore assessed a broad sample of 38 autistic children on the preeminent test of fluid intelligence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
287
2
35

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(347 citation statements)
references
References 24 publications
23
287
2
35
Order By: Relevance
“…They are considered to be culturally fair power tests and are often used as unidimensional measures of fluid intelligence. Recently, Dawson et al (2007) reported children and adults with autism to score about 30 percentile points higher on the RPM than on the WIS. As the authors deem the RPM a paramount metric of reasoning and problem solving, and therefore a valid measure of general IQ, they conclude that intelligence has been underestimated in individuals with autism. Put differently, this conclusion suggests that while RPM do allow fair IQ testing in autism, the WIS do not, which would dispute the utility of the WIS as the standard IQ measure for clinical or research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered to be culturally fair power tests and are often used as unidimensional measures of fluid intelligence. Recently, Dawson et al (2007) reported children and adults with autism to score about 30 percentile points higher on the RPM than on the WIS. As the authors deem the RPM a paramount metric of reasoning and problem solving, and therefore a valid measure of general IQ, they conclude that intelligence has been underestimated in individuals with autism. Put differently, this conclusion suggests that while RPM do allow fair IQ testing in autism, the WIS do not, which would dispute the utility of the WIS as the standard IQ measure for clinical or research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Wszelkie próby podkreślenia jego odrębności są odbierane jako zagrożenie i prowokują reakcje obronne. 9 Fuzja z matką daje złudzenie poczucia bezpieczeństwa, stąd dzieci te usilnie próbują utrzymać iluzję fizycznej jedności. Senator w swoim artykule podaje przykłady ilustrujące wysiłki dziecka zmierzające w kierunku utrzymania poczucia symbiozy z matką.…”
Section: Wprowadzenieunclassified
“…Istotna rozbieżność w diagnozie funkcjonowania intelektualnego Kuby, wynikająca z zastosowania różnych metod diagnostycznych, znajduje odzwierciedlenie w badaniach prowadzonych przez Dawson et al 9 Diagnozując możliwości umysłowe dzieci i dorosłych z autyzmem za pomocą Testu Wechslera i Testu Matryc Ravena, naukowcy ci zinterpretowali rozbieżności w ocenie funkcjonowania intelektualnego badanych jako wynik niewłaściweg doboru metod diagnostycznych (Test Matryc Ravena opiera się w całości na obrazach, skala Wechslera wymaga kompetencji słowno-językowych i społecznych), co wią-że się z ryzykiem niedoceniania potencjału umysłowego osób ze spektrum autystycznego. 12 Zabawa z pojemnikami, która tak intensywnie zajmowała Kubę, mogłaby się wydawać nieadekwatna do prezentowanego przez chłopca poziomu rozwoju poznawczego.…”
Section: Omówienieunclassified
“…Instead of using just the Wechsler IQ tests, they tested both normal and autistic children with Raven's Progressive Matrices (Dawson et al 2007). In this test, the person is shown complicated patterns and he/she has to choose the pattern that will complete a series of patterns.…”
Section: Autistic Intelligencementioning
confidence: 99%